Major Fungal Diseases of Rice: A Case Study - Samal, Suchismita; Parida, Sagarika (Asian Journal of Biological and Life Sciences)
Disease screening and evaluation is a major parameter for measurement of host resistance of various rice germplasm and this study will facilitate for genetic mapping of resistance genes for researchers. The survey work was carried out on rice fields in National Rice Research Institute, Cuttack, to evaluate the distribution of different fungal diseases on various rice cultivars. Disease occurrence percentage was calculated as the proportion of cultivars showing the symptoms of a particular disease, out of total number of cultivars assessed. Fourteen different cultivars were namely CG (2090/226), Dhalaswarna, Tapaswini, TRB 1949, TRB 1156, TN1, BA115, BA90, BA13, Ajay 2006, Pradhandhan, M313 and aerobic variety assessed based on disease prevalence. Six different diseases were observed during the study period viz., sheath rot, sheath blight, false smut, blast, brown spot and bakane. Identification of these diseases was based on the specific morphological symptoms on leaves and other infected parts of these rice cultivars. Methods of isolation of casual organism and their colony character were also observed during survey in department of plant pathology. It was found that in the month of October four fungal diseases are most prevalent. These are blast, sheath blight, sheath rot and Bakanae. At the end of November false smut and brown smut symptoms were found. Among these diseases, leaf blast was found as the most prevalent disease at vegetative growth stage as it affected highest number of cultivars. Among these, blast is found to be more prevalent disease with 35.71% of occurrence which is caused by fungus Magnoporthe oryzae followed by sheath blight and sheath rot. Brown spot and bakane disease was found each with least percentage of occurrences.
Keywords: Bakane; Casual organisms; Fungal diseases; Host resistance; Oryzae sativa; symptoms